NOTES ON PTEROCYMBIUM R. BR. (STERCULIACEAE) - KOSTERMANS, A. J. G. H. (REINWARDTIA, 1950)
For the Malaysian region three species and one variety of Pterocymbium are recognized,viz. P. beccarii K. Schumann, P.tinctorium (Blanco)Merrill,with var.javanicum(R. Brown) Kostermans and P.tubulatum (Masters) Pierre. Pterocymbium parviflorum Merrill is reduced to P. tubulatum; P. eamvanulatum Pierre,P.macrocrater Warburg,and P.viridiflorum Koorders are reduced to P. tinc- torium;P. stipitatum White & Francis is reduced to P.beccarii; whereas P.javanicum R.Brown is reduced to a variety of P.tinctorium,Pterocymbium tinctorium var.java- nicum (R. Brown) Kostermans var. nov.An enumeration of the specimens examined follows upon the annotations to each of the species recognized. Pterocymbium gigantifolium Elmer is referred to Sterculia L.under the name of Sterculia membranifolia Kostermans nom. nov.